Answer:
(x + 2) + (–5x + 4) / (x² – 2x + 1)
Step-by-step explanation:
(x³ – 8 x + 6) ÷ (x² – 2x + 1)
The operation can be carried out as follow:
Please see attached photo for details.
(x³ – 8 x + 6) ÷ (x² – 2x + 1) =
(x + 2) + (–5x + 4) / (x² – 2x + 1)
Answer:
negative
slope= -1/4
Step-by-step explanation:
We have that
x²<span>-6x+7=0
</span>Group terms that contain the same variable
(x²-6x)+7=0
Complete the square Remember to balance the equation
(x²-6x+9-9)+7=0
Rewrite as perfect squares
(x-3)²+7-9=0
(x-3)²-2=0
(x-3)²=2
(x-3)=(+/-)√2
x=(+/-)√2+3
the solutions are
x=√2+3
x=-√2+3
Answer:
Your answer would be
![1 \times 3 = 3](https://tex.z-dn.net/?f=1%20%5Ctimes%203%20%3D%203)
And
![3 \times 5 = 15](https://tex.z-dn.net/?f=3%20%5Ctimes%205%20%3D%2015)
Step-by-step explanation:
Hope this helps. If I am wrong, REPORT ME PLEASE.
<span><span>12</span> + <span>15</span> + <span>45</span> + 1 <span>23</span> = <span>196</span> = 3<span>16</span> ≅ 3.166667</span>